Highly efficient utilization of industrial barium slag for carbon gasification in direct carbon solid oxide fuel cells. (26th October 2021) - Xie, Yujiao; Sun, Zhongyuan; Han, Tingting; Xie, Ziheng; Zhang, Jinjin; Sun, Haibin; Xiao, Jie; Wang, Yishang; Yu, Fangyong; Yang, Naitao
Abstract: Direct carbon solid oxide fuel cells (DC-SOFCs) are recognized as an efficient energy conversion device. With regard to their operation mechanism, the reverse Boudouard reaction rate is the crucial factor influencing cell performance. In this work, a new-type catalyst derived from industrial barium slag (BS) was first developed to enhance the reverse Boudouard reaction and DC-SOFC performance. The chemical composition and micro-morphologies of BS and barium slag-derived catalyst (BSC) were characterized in detail. The superiorities of BS and BSC were reflected in the enhanced DC-SOFC performance and high fuel utilization. The single cell fueled by BSC-loaded carbon yielded the best output of 249 mW cm −2  at 850 °C. This result was comparable to the 266 mW cm −2 output of a hydrogen-fueled SOFC due to the superior catalytic activity of metallic catalysts toward carbon gasification. The advantage of the BSC was also observed in the durable operation of the corresponding DC-SOFCs, which lasted for 36.2 h at 50 mA with the fuel utilization of 29.0%. This work provides a new channel for green and efficient utilization of BS and other industrial residues, and a novel option to the development of energy conversion technology. Highlights: Barium slag is first introduced in DC-SOFCs to improve electrochemical performance. There are many superior metallic catalysts for carbon gasification in barium slag. DC-SOFC output is improved from 178 to 249 mW cm −2  by barium slag-derived catalyst. DC-SOFC fueled by BSC-loaded carbon is comparable to the hydrogen-fueled SOFC. BSC-loaded carbon-fueled DC-SOFC operates for 36.2 h with fuel utilization of 29.0%.